A Comparison of Puncture and Continuous Pump Analgesia With Two Different Approaches to Thoracic Paravertebral Block for Thoracic Surgery - Huang, Qiao-wen; Lu, Zhi-wei; Li, Jia-bin; Zhang, Wen-qing; Jiang, Li-wei; Lin, Zhi-jian (Frontiers in Surgery, 2022)
Background This study aims to compare the success rate of thoracic paravertebral block (TPVB) and the effect of postoperative analgesia between two approaches. Methods A total of 34 patients with American Society of Anesthesiology (ASA) physical status score II–III, undergoing an optional thoracoscopic surgery, were randomly assigned to a parasagittal approach group (group P, n = 17) and a transverse intercostal approach group (group T, n = 17). The catheterization time, success rate of the puncture and catheterization, block plane and effect at the surgical site were compared between two groups. The mean arterial pressure and heart rate were recorded, as well as the cold tactile block plane and numeric rating scale (NRS) at 0.5, 2, 4, 8, 12, 24, and 48 h after surgery. The study was registered at http://www.chictr.org.cn/showproj.aspx?proj=9624 (Registration number: ChiCTR2100054642). Results The catheterization time in group P was significantly longer than that in group T (P < 0.05). The success rate of catheterization in group P was lower than that in group T, but no statistical significance (P = 0.085). There was no significant difference in the success rate of Puncture and blocking effect of the surgical site at 30 min post-injection between two groups (P > 0.05). There was no significant difference in the cold tactile block plane and NRS scores during coughing between two groups at 0.5, 2, 4, 8, 12, 24, and 48 h postoperatively (P > 0.05). Conclusion This study suggests that there is no significant difference in postoperative block level or pain score during coughing for thoracoscopic surgery between ultrasound-guided parasagittal and transverse intercostal approach, but the parasagittal approach takes longer and has a higher failure rate.